Producción de hidrocarburos líquidos y gaseosos mediante la colicuefacción térmica del carbón mineral con residuos de polietileno de baja densidad (2007)
In this work, it was performed a thermal liquefaction of a sub-bituminous coal from La Yolanda colliery (Valle del Cauca) with low density polyethylene waste in presence of tetraline and hydrogen. Experimental conditions used were a batch reactor of 115 ml magnetically stirred, temperatures of 380, 400, 420C, mass relation coal/poliethylene/tetraline of 1/5/3 and residence time of 30 minutes. Results showed that for the thermal coliquefaction using tetraline, conversion decrease with increase of temperature, whereas oils, asphaltenes, preasphaltenes and selectivity have a contrary behavior. Results also showed that, at 400 C, both high conversion and asphaltenes concentration were obtained using coal and waste polyethylene only. However, at those conditions selectivity to oils was lower than 20%.